Post-operative aural surgical wound dressing in rats (Journal of Laboratory Animal Science, 2022)
Wound dressing is an integral technique of animal care in various studies involving animal models. This post-operative  technique often determines the mortality and morbidity of the animal used and also influences experimental outcomes. Post  auricular surgical wounds presents a challenge for dressing on account of presence of sense organs in the vicinity. Rats are  also prone to damaging the dressing and the underlying sutures. Hence, an appropriate technique for dressing the region  is vital for successful surgical outcomes. Literature on dressing of post auricular surgical wounds in rats are scarce. The  present work describes in detail the wound dressing technique in adult Wistar rats developed by the authors. A total of 14  animals were used for the study and with this technique, the wrap around the incision was found to be intact till the next  day of post-operative dressing. The wound healing process appeared to be normal with no visible signs of infection at the  incision.
Keywords: Post-operative; Wistar rats; wound dressing